Decorticating hungry rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Decorticating hungry rice is an arduous task which is usually done with a pestle after the grain has been mixed with sand.